Identification and validation of a prognostic-related mutant gene DNAH5 for hepatocellular carcinoma - Song, Zebing; Song, Xiaodong; Li, Hang; Cheng, Zongbing; Mo, Zengyi; Yang, Xuewei (Frontiers in Immunology, 2023)
Background: Hepatocellular carcinoma (HCC) contribute to one of the major cancer-related death worldwide with a worse prognosis. Thus, there needs an effective biomarker to improve, and predict the prognosis of HCC. Methods: RNA-sequencing data, simple nucleotide variation data, and clinical data of HCC patients from The Cancer Genome Atlas to identify mutant genes, simple nucleotide variation data, and clinical data of HCC patients from the International Cancer Genome Consortium to validate the prognostic value of mutant genes were the data source of the present study. To identify overall survival (OS) related mutant genes, Kaplan-Meier analysis was performed. We performed univariate Cox and multivariate Cox regression analysis to identify independent prognostic factors. We also performed correlation analysis among immune cells and mutant genes. To explore the molecular mechanisms of mutant genes, we performed the gene sets enrichment analysis (GSEA). A nomogram was constructed to help predict the prognosis of HCC. In addition, we explored the expression profile of mutant gene in HCC based on TCGA set, ICGC set and our own HCC tissues. Results: We identified and validated a mutant gene DNAH5 which was negatively related to the OS of HCC. Univariate Cox and multivariate Cox regression analysis revealed that mutant gene DNAH5 could act as an independent prognostic factor of HCC. Most pathways of mutant gene DNAH5 were involved in cancer development and progression based on GSEA analysis. Mutant gene DNAH5 was negatively relevant to Monocytes, T cells CD4 naive, Dendritic cells activated, and Mast cells activated. In addition, the mRNA and protein level of DNAH5 was a significantly higher expression in HCC tissues. A nomogram consisting of the pathological stage, DNAH5, and TMB performed well. Conclusion: Mutant gene DNAH5 was a significantly higher expression in HCC tissues and could act as an independent prognostic factor for HCC, and maybe a new potential immunotherapy target of HCC.